Modulating effect of MgO-SiO2 nanoparticles on immunological and histopathological alterations induced by aflatoxicosis in rats. (15th December 2017) - Essa, Sara S.; El-Saied, Eiman M.; El-Tawil, Osama S.; Mahmoud, Manal B.; Abd El-Rahman, Sahar S.
Abstract: Introduction: AflatoxinB1 (AFB1) is well-known as a feed borne-hepatotoxic and immunosuppressive mycotoxin. This study was conducted to evaluate the efficacy of nanocomposite magnesium oxide and silicon oxide (MgO-SiO2 ) in reducing the toxic effects of AFB1on the immunity and histological alterations in liver, spleen and intestine of adult male rats. Experimental design: Animals were divided into a control (Gp1) and three experimental groups (Gps); Gp2 received feed contained 200 ppb AFB1, Gp3 received feed contained 200 ppb AFB1 and 0.5 g/kg MgO-SiO2 nanocomposite. While, rats of Gp4 received feed contained 0.5 g/kg MgO-SiO2 nano-composite. Methods: Cellular and humoral immune responses, as well as histopathological examination and caspase-3 expression in liver, spleen, and intestine, were all evaluated. Residual concentration of AFB1was determined in serum, liver and fecal samples. The obtained data were statistically analyzed. Results: AFB1markedly reduced body weight gain and food and water consumption. Cellular immune response (total and differential leukocytes count, neutrophils' phagocytic activity, lymphocyte transformation, macrophage activity and serum lysozyme activity), serum total protein, and humoral immune response (fractions of protein as estimated by SDS- PAGE electrophoresis) were all severely reduced by AFB1. Moreover, AFB1induced marked histological alterations and apoptosis in liver, spleen, and intestine. Conclusion: These findings suggested that the nanocomposite MgO-SiO2 has high affinity to adsorb AFB1 and can effectively modulate its toxicity in rats. Impact statement: Nanocomposite MgO-SiO2 may offer a novel effective and cheap approach for the preventive management of aflatoxicosis in animals. Graphical abstract: Highlights: MgO-SiO2 nanoparticles amend the effect of aflatoxicosis on immune responses. Nanocomposite of MgO-SiO2 (NC) could be considered as an adsorbing agent for AFB1. NC ameliorates histological alterations of aflatoxicosis on liver, spleen, and intestine. NC can be a cheap, safe and accessible animal feed additive to prevent aflatoxicosis.